TRATAMENTO AVANÇADO DE EFLUENTE DE INDÚSTRIA DE PAPEL E CELULOSE POR PROCESSOS DE COAGULAÇÃO E ULTRAFILTRAÇÃO - GAVINO, WILLERSON RAPHAEL GIACOMITTI (2016)
The effluents generated in the pulp and paper industry have a high load of recalcitrant pollutants such as organochlorine compounds and phenolic compounds, besides presenting high color and COD and high solids concentration. These dissolved toxic pollutants are not efficiently removed by secondary treatment processes usually employed in the wastewater treatment plant. Therefore, this study aimed to propose two alternatives of advanced treatment for this type of effluent, coagulation, with a tannin-based reagent, and Ultrafiltration. The dosage of 160 mg/L of coagulant Acquapol S5T, with 10 minutes settling time, was able to achieve apparent color and turbidity reduction above 97%, 98% removal of TSS and 64.5% of phenols. UF achieved more than 99% reductions of turbidity, apparent color removal in 90%, COD reduction of 89% and 76% of total phenols. In addition to the analysed parameters, it was also evaluated the performance of the backwashing in recovery of the permeate flux, which proved to be very important to maintain a high degree of permeability in the membrane.